The Arctic Lobby in Japan: Structures, Mechanisms of Infl uence and the Role in Developing Cooperation with the Russian Federation - E. V. Polkhova; A. A. Sergunin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Japan’s Arctic strategy, particularly its geopolitical and economic aspects, has been thoroughly reviewed by both Russian and foreign experts. However, the structures and mechanisms behind this strategy remain somewhat obscure. This paper is intended to partially fill this gap by resorting to the study of the Japanese Arctic lobby. The authors identify the key interest groups which stand for an active Arctic policy and for cooperation with the Russian Federation in that regard. These include, in particular, the energy sector representatives that sought to take part in the construction of liquefied natural gas (LNG) plants. The decision of the Japanese government to join the Western anti-Russian sanctions disrupted these plans. However, the adoption of S. Abe’s 8-points plan in 2016 opened up new opportunities for the Russia-Japan Arctic cooperation. Yet another two groups of interest are equally interested in strengthening bilateral relations — shipping and ship-building industries. They also suffered from anti-Russian sanctions but now they are actively engaged in the construction of the LNG jetties near Murmansk and in Kamchatka. There is also a growing interest towards the Arctic region within the fishery industry — a very important sector of Japan’s economy. Cooperation with Russia increases Tokyo’s capacity to participate in the creation of international legal regime of fisheries in the Central Arctic ocean. Finally, the authors identify another important element of the Japanese Arctic lobby — regional elites. In that regard, they examine activities of the Hokkaido prefecture to engage in development of the Northern Sea Route. The paper examines the key mechanisms used by the Arctic lobby to influence the authorities, including sectoral, regional and national business associations, research and educational centers and mass media, as well as ‘built-in lobby’ in relevant ministries and agencies responsible for making and implementing Tokyo’s Arctic policies. The authors conclude that, although the Arctic lobby is unable to persuade the Government to remove anti-Russian sanctions altogether, elaboration of a selective strategy of cooperation with the Japanese business community could strengthen bilateral relations and provide new opportunities for exploiting natural resources of the Far North and developing the Russian Arctic.